ANALISIS KESALAHAN BERBAHASA PADA BUKU SISWA PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS VI SD DI ACEH BESAR - Wahidah Nasution (Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Textbook is one of the written works in the form of a book, intended to discuss a certain field which becomes a standard book for teachers and students in the learning process for instructional purposes and objectives, which is equipped with suitable teaching facilities and is easily understood by the users in schools. schools so that they can support teaching programs. The quality of books must be a concern for all parties because books are the main learning tool. This can be started from the use of language contained in the book. This study aims to find out the language errors contained in the class VI student book